Right nonrecurrent laryngeal nerve: a surgical trap - Patil, Vasanthi; D. S., Akshay; Borewad, Ganesh (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2024)
Head and neck surgeons must be aware of Non recurrent laryngeal nerve, a rare entity, to avoid postoperative morbidity. In this case report, a 38-year-old female who underwent thyroid surgery and a right non-recurrent laryngeal nerve was identified intra-operatively were reported.